Phylogenetic analysis, homology modelling, molecular dynamics and docking studies of caffeoyl-CoA-O- methyl transferase (CCoAOMT 1 and 2) isoforms isolated from subabul (Leucaena leucocephala) - Pagadala, Nataraj Sekhar; Arha, Manish; Reddy, P. S.; Kumar, Ranadheer; Sirisha, V. L.; Prashant, S.; Reddy, K. Janardhan; Khan, Bashir Mohammad; Rawal, S. K.; Kishor, P. B. Kavi (Journal of Molecular Modeling, 2009)
Caffeoyl coenzyme A O-methyltransferase (CCoAOMT) is an important enzyme that participates in lignin biosynthesis especially in the formation of cell wall ferulic esters of plants. It plays a pivotal role in the methylation of the 3-hydroxyl group of caffeoyl CoA. Two cDNA clones that code CCoAOMT were isolated earlier from subabul and in the present study; 3D models of CCoAOMT1 and CCoAOMT2 enzymes were built using the MODELLER7v7 software to find out the substrate binding sites. These two proteins differed only in two amino acids and may have little or no functional redundancy. Refined models of the proteins were obtained after energy minimization and molecular dynamics in a solvated water layer. The models were further assessed by PROCHECK, WHATCHECK, Verify_3D and ERRAT programs and the results indicated that these models are reliable for further active site and docking analysis. The refined models showed that the two proteins have 9 and 10 alpha-helices, 6 and 7 beta-sheets respectively. The models were used for docking the substrates CoA, SAM, SAH, caffeoyl CoA, feruloyl CoA, 5-hydroxy feruloyl CoA and sinapyl CoA which showed that CoA and caffeoyl CoA are binding with high affinity with the enzymes in the presence and absence of SAM. It appears therefore that caffeoyl CoA is the substrate for both the isoenzymes. The results also indicated that CoA and caffeoyl CoA are binding with higher affinity to CCoAOMT2 than CCoAOMT1. Therefore, CCoAOMT2 conformation is thought to be the active form that exists in subabul. Docking studies indicated that conserved active site residues Met58, Thr60, Val63, Glu82, Gly84, Ser90, Asp160, Asp162, Thr169, Asn191 and Arg203 in CCoAOMT1 and CCoAOMT2 enzymes create the positive charge to balance the negatively charged caffeoyl CoA and play an important role in maintaining a functional conformation and are directly involved in donor-substrate binding.
Keywords: Caffeoyl-CoA 3-O-methyl transferase; docking; Modelling; S-adenosyl homocysteine

Design, synthesis and evaluation of unique 2,4,5-triaryl imidazole derivatives as novel potent aspartic protease inhibitors - Khan, Mohd Sajid; Akhtar, Salman; Siddiqui, S. A.; Siddiqui, M. S.; Srinivasan, K. V.; Arif, J. M. (Medicinal Chemistry, 2012)
The 2,4,5-triaryl imidazole derivatives (API) were designed, screened and characterized kinetically & thermo-dynamically against Pepsin and their activity was also tested on the in silico platform. The docking studies of API with Pepsin show that these are novel and unique inhibitors of Aspartic protease. Drug like properties of these compounds were validated in silico based on Lipinski's rule of Five by calculating ClogP, LogS, H-bond acceptors, H-Bond donors, rotational bonds, PSA, PB and BBB values. The Et/Ki and Et/Km values of API show that they follow the Michaelis-Menten kinetics. The binding of inhibitors with proteases was explained by using Van't Hoff plot and thermodynamic parameters viz. free energy (Delta G), Entropy (Delta S) and Enthalpy (Delta H). The Van't Hoff analysis showed that the value of K-i decreases with increase in temperature and the binding of the inhibitor are entropically driven. API act as new potent aspartic protease inhibitors with K-i, for Pepsin, ranges from 3.7 mu M to 16.7 mu M. Strong hydrophobic groups at C-4 & C-5 position in API favor binding of inhibitors with Pepsin. Experiments also showed that among C-2 aryl substituted imidazole, a 4-substitution on aryl ring is preferred and less polar substituent makes the molecule more active whereas polar substituents at 2-position on C-2 aryl ring makes the molecule less active. The docking studies of API with Pepsin further intensify and validate our results.
Keywords: 2; 4; 5-triaryl imidazole derivatives; docking; Lipinski's rule of Five; Protease inhibitors; Thermodynamics

Design, synthesis, structural characterization by IR, 1H, 13C, 15N, 2D-NMR, X-ray diffraction and evaluation of a new class of phenylaminoacetic acid benzylidene hydrazines as pfENR inhibitors - Samal, Ramanuj P.; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Bwalya, Angela Gono; Tasdemir, Deniz; Joshi, Ramesh A.; Rajamohanan, P. R.; Puranik, Vedavati G.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2013)
Recent studies have revealed that plasmodial enoyl-ACP reductase (pfENR, FabI), one of the crucial enzymes in the plasmodial type II fatty acid synthesis II (FAS II) pathway, is a promising target for liver stage malaria infections. Hence, pfENR inhibitors have the potential to be used as causal malarial prophylactic agents. In this study, we report the design, synthesis, structural characterization and evaluation of a new class of pfENR inhibitors. The search for inhibitors began with a virtual screen of the iResearch database by molecular docking. Hits obtained from the virtual screen were ranked according to their Glide score. One hit was selected as a lead and modified to improve its binding to pfENR; from this, a series of phenylamino acetic acid benzylidene hydrazides were designed and synthesized. These molecules were thoroughly characterized by IR, 1H, 13C, 15N, 2D-NMR (COSY, NOESY, 1H-13C, 1H-15N HSQC and HMBC), and X-ray diffraction. NMR studies revealed the existence of conformational/configurational isomers around the amide and imine functionalities. The major species in DMSO solution is the E, E form, which is in dynamic equilibrium with the Z, E isomer. In the solid state, the molecule has a completely extended conformation and forms helical structures that are stabilized by strong hydrogen bond interactions, forming a helical structure stabilized by N-H...O interactions, a feature unique to this class of compounds. Furthermore, detailed investigation of the NMR spectra indicated the presence of a minor impurity in most compounds. The structure of this impurity was deduced as an imidazoline-4-one derivative based on 1H-13C and 1H-15H HMBC spectra and was confirmed from the NOESY spectra. The molecules were screened for in vitro activity against recombinant pfENR enzyme by a spectrophotometric assay. Four molecules, viz. 17, 7, 10, and 12 were found to be active at 7, 8, 10, and 12m concentration, respectively, showing promising pfENR inhibitory potential. A classification model was derived based on a binary QSAR approach termed recursive partitioning (RP) to highlight structural characteristics that could be tuned to improve activity.
Keywords: ADMET; docking; enoyl-ACP reductase; FabI; hydrogen bonding; NMR; phenylaminoacetic acid benzylidene hydrazine; Plasmodium falciparum; Plasmodium falciparum enoyl-ACP reductase; QSAR; recursive partitioning; X-ray diffraction

Structural modelling of substrate binding and inhibition in penicillin V acylase from pectobacterium atrosepticum - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Suresh, C. G.; Pundle, Archana V.; Ramasamy, Sureshkumar (Biochemical and Biophysical Research Communications, 2013)
Penicillin V acylases (PVAs) and bile salt hydrolases (BSHs) have considerable sequence and structural similarity; however, they vary significantly in their substrate specificity. We have identified a PVA from a Gram-negative organism, Pectobacterium atrosepticum (PaPVA) that turned out to be a remote homolog of the PVAs and BSHs reported earlier. Even though the active site residues were conserved in PaPVA it showed high specificity towards penV and interestingly the penV acylase activity was inhibited by bile salts. Comparative modelling and docking studies were carried out to understand the structural differences of the binding site that confer this characteristic property. We show that PaPVA exhibits significant differences in structure, which are in contrast to those of known PVAs and such enzymes from Gram-negative bacteria require further investigation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bile salt hydrolase; docking; Homology modelling; Inhibition; Pectobacterium; Penicillin acylase

Pharmacophore and docking based virtual screening of validated mycobacterium tuberculosis targets - Vyas, Renu; Karthikeyan, Muthukumarasamy; Nainaru, Ganesh; Muthukrishnan, Murugan (Combinatorial Chemistry & High Throughput Screening, 2015)
Target based virtual screening has surpassed ligand based virtual screening methods in the recent past mainly as it provides more clues regarding intermolecular interactions and takes into consideration the flexible receptor as well. The current methodology describes a computational strategy of predicting Mycobacterium tuberculosis (M. tuberculosis) binders for five well studied targets representing M. tuberculosis proteome encompassing most of the known mechanisms of action. The diversity of the targets was affirmed by their active site analysis and structural studies. The current approach employed pharmacophore searching, docking and clustering techniques in tandem and was validated by enrichment studies using the available Schrodinger data set consisting of 1000 decoys. The application of this methodology was demonstrated by predicting potential molecular targets for fifty newly synthesized compounds. Cross docking studies on the targets were carried out with 4512 known inhibitors utilizing a high performance computing platform to reveal underlying affinity and promiscuity patterns. Optimum binding energy range for all targets as determined by high throughput docking was found to be -3 to -13 kcal/mol.
Keywords: Binding energy; docking; Mycobacterium tuberculosis; open source drug discovery (OSDD); pharmacophore; structure based drug design (SBDD)

Structural-functional insights and studies on saccharide binding of Sophora japonica seed lectin - Yadav, Priya; Shahane, Ganesh; Ramasamy, Sureshkumar; Sengupta, Durba; Gaikwad, Sushama (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of the Sophora japonica seed lectin (SJL) were studied in detail using bioinformatics and biophysical tools. Homology model of the lectin displayed all the characteristics of the legume lectin monomer and the experimental observations correlated well with the structural information. In silico studies were performed by protein-ligand docking, calculating the respective binding energies and the residues involved in the interactions were derived from LigPlot(+) analysis. Fluorescence titrations showed three times higher affinity of T-antigen disaccharide than N-acetyl galactosamine (GaINAc) towards SJL indicating extended sugar binding site of the lectin. Thermodynamic parameters of T-antigen binding to SJL indicated the process to be endothermic and entropically driven while those of GaINAc showed biphasic process. SDS-PAGE showed post-translationally modified homotetrameric species of the lectin under native conditions. In presence of guanidine hydrochloride (0.5-5.0 M), the tetramer first dissociated into dimers followed by unfolding of the protein as indicated by size exclusion chromatography, fluorescence and CD spectroscopy. Different structural rearrangements were observed during thermal denaturation of SJL at physiological pH 7.2, native pH 8.5 and molten globule inducing pH 1.0. Topological information revealed by solute quenching studies at respective pH indicated differential hydrophobic environment and charge density around tryptophan residues. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Dissociation; docking; Homology model; Ligand binding; Sophora japonica seed lectin; Thermal transitions

Synthesis and docking studies of pyrazine-thiazolidinone hybrid scaffold targeting dormant tuberculosis - Chitre, T. S.; Asgaonkar, K. D.; Miniyar, P. B.; Dharme, A. B.; Arkile, Manisha A.; Yeware, A.; Sarkar, Dhiman; Khedkar, Vijay M.; Jha, Prakash C. (Bioorganic & Medicinal Chemistry Letters, 2016)
The persistence of Mycobacterium tuberculosis (MTB) in dormant stage assists the pathogen to develop resistance against current antimycobactrial drugs. To address this issue, we report herein the synthesis of N-(4-oxo-2 substituted thiazolidin-3yl) pyrazine-2-carbohydrazide derivatives designed by following the molecular hybridization approach using pyrazine and thiazolidenone scaffolds. The compounds were evaluated against MTB H37Ra and Mycobacterium bovis BCG in dormancy model. Most of the compounds had IC50 values in 0.3-1 mu g/ml range. The active compounds were further tested for anti-proliferative activity against THP-1, Panc-1, A549, and MCF-7 cell lines using MTT assay and exhibited no significant cytotoxicity. We also report molecular docking studies using active analogs and MTB Decaprenylphosphoryl-beta-D-ribose-2'-epimerase (DprE1) to rationalize the biological activity and to provide an insight into the probable mechanism of action and binding mode of hybridized structures. The results obtained validate the use of molecular hybridization approach and also suggest that reported compounds can provide a novel pharmacophore to synthesize lead compounds against dormat MTB. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: docking; Dormant; Hybrid design; Pyrazine; Thiazolidenone; tuberculosis

Vitro and in silico antifungal efficacy of nitrogen- doped carbon nanohorn ( NCNH) against rhizoctonia solani - Dharni, Seema; Sanchita; Unni, SreeKuttan M.; Kurungot, Sreekumar; Samad, Abdul; Sharma, Ashok; Patra, Dharani Dhar (Journal of Biomolecular Structure & Dynamics, 2016)
We have investigated in vitro antifungal efficiency of nitrogen-doped carbon nanohorn (NCNH) against Rhizoctonia solani (R. solani) plant pathogenic fungi. NCNH with size of 50-60nm and concentrations of 10, 50, 100, and 150gmL(-1) were used. The results showed that growth of fungi in the presence of NCNH was significantly (p>.05) inhibited at 150gmL(-1) (85.13 +/-.97) after 72h. The results were validated through computational approaches. Molecular docking analysis of NCNH with endochitinase protein of R. solani was performed to validate the potential of antifungal activity of NCNH. Docking results showed different conformations of interaction of NCNH with endochitinase enzyme. The conformation with least binding energy -13.54kcal/mol was considered further. It is likely that NCNH interacts with the pathogens by mechanically wrapping, which may be one of the major toxicity actions of NCNH against R. solani. The analysis showed that NCNH might interwinds to endochitinase of R. solani leading to the deactivation of the enzyme. To best of our knowledge, this is the first report of antifungal efficacy of NCNH against R. solani and provides useful information about the application of NCNH in resisting crop disease.
Keywords: docking; endochitinase; nitrogen-doped carbon nanohorn; Rhizoctonia solani

Molecular characterization of the beta(2)-like octopamine receptor of helicoverpa armigera - Gujar, Nidhi; Nikte, V, Siddhanta; Joshi, Rakesh S.; Joshi, Manali (Journal of Membrane Biology, 2021)
Helicoverpa armigera is a devastating polyphagous and cosmopolitan crop pest. There are reports of this insect being resistant to a variety of pesticides raising concern worldwide. The Octopamine (OA) binding beta(2)-like receptor (OAR), a GPCR, is widely distributed in the nervous system of the insect and plays essential roles in the physiology and development and thus is an important target for insecticides. Yet, the molecular characterization of the H. armigera OAR (HarmOAR) and rational design of compounds based on this receptor is lacking. As a first step, we performed multiple sequence alignment of all insect OARs, which revealed that the sequences contained all conserved class A GPCR motifs. Phylogenetic studies showed clade-specific variations in the protein sequences primarily arising owing to differences in the ICL3 loop region. Further, a structural model of HarmOAR was built using the inactive human beta(2)AR as a template. 0.9 mu s atomistic simulations revealed conserved inter helical contacts and water molecules of HarmOAR. The detailed binding of octopamine was studied using molecular docking and 0.3 mu s atomistic simulations. Twenty-two insecticides active against octopamine receptors of other insects were compiled and docked to HarmOAR followed by rescoring with binding free energies to prioritize them for H. armigera. Our study suggests alpha-terpineol to be a good candidate as an insecticide or insect repellent for Helicoverpa armigera.
Keywords: docking; Helicoverpa armigera; Insecticides; molecular dynamics; Octopamine receptor; Phylogeny

Pharmacore maping based on docking, ADME/toxicity, virtual screening on 3,5-dimethyl-1,3,4-hexanetriol and dodecanoic acid derivates for anticancer inhibitors - Prakash, Palanisamy; Vijayasarathi, Durairaj; Selvam, Kuppusamy; Karthi, Sengodan; Manivasagaperumal, Rengarajan (Journal of Biomolecular Structure & Dynamics, 2021)
Plants produced natural generating products play a significant role in drug discovery of new bioactive compounds and these are used for advancement of innovative curative drugs for specific target health diseases. In this study Docking and ADME/T virtual screening method are apply for in drug discovery and can be divided into ligand- and target structure-based. The aim of this study was to analyze theDecalepis hamiltoniiisolated compounds by using the evaluation of molecular docking and virtual screening of anticancer drugs. MOE docking ADME/Toxicity and virtual screening approaches. A docking energy -12.97 kcal/mol; -9.93- kcal/mol on cancer responsible protein was targeted. Further, the compounds were filtered through the rule of five, ADME/Toxicity risk and synthetic accessibility. The active compound were then docked to recognize the possible target binding pocket to obtain a set of a ligand poses and to prioritize the predicted active compounds. The scrutinize compounds, as well as their metabolites were evaluated for different pharmacokinetics parameter such as ADME/Toxicity. Therefore, the result shows that a large number of compounds were found to be ADME/toxicity positive to be a positive drug molecule against cancer, selected compounds under study satisfies parameters for ADME and Toxicity properties. The present study demonstrate to identifying the novel structures which are having similar structural feature with like activity with respect to the compounds 3,5-Dimethyl-1,3,4-Hexanetriol and Dodecanoic acid that are shown best binding energy with the receptors 4igk and 4b3z respectively. This study may provide significant clues for discovery novel drug inhibitors for cancer properties.
Keywords: ADME; Decalepis hamiltonii; docking; drug discovery; Toxicity; virtual screening

First synthesis of podocarflavone A and its analogs and evaluation of their antimycobacterial potential against mycobacterium tuberculosis with the support of virtual screening - Puranik, Ninad V.; Swami, Sagar; Misar, Ashwini V.; Mamgain, Ritu; Gulawani, Swapnaja S.; Dhiman, Sarkar; Srivastava, Pratibha (Natural Product Research, 2022)
The first synthetic route developed for Podocarflavone A reported from Podocarpus macrophyllus and its analogs in 7 steps. Computational analysis for binding with the pantothenate kinase (3AVO) of Mycobacterium tuberculosis showed their docking score (ds) in the range of -8.9 to -9.3 Kcal/mol. MD simulations delineated the stability of the protein-ligand complexes in the TIP3P model. MMGBSA and MMPBSA values of 8d were -42.46 Kcal/mol and -14.58 Kcal/mol, respectively. Further in-vitro antitubercular screening of compounds 8a, 8d, and 8e against M. tuberculosis H37Ra using XRMA protocol exhibited promising antimycobacterial activity with IC50 values 21.82 mu g/mL, 15.55 mu g/mL, and 16.56 mu g/mL, respectively. Compounds 8a, 8d, and 8e showed antibacterial activity with IC50 values 41.56 mu g/mL, 24.72 mu g/mL, and 72.45 mu g/mL respectively against the Staphylococcus aureus. 8a and 8d showed inhibition with IC50 values 39.6 mu g/mL and 27.64 mu g/mL, respectively, against Bacillus subtilis. The present study could help in the further development of lead molecules against tuberculosis.
Keywords: and MMGBSA; antimycobacterial activity; docking; MD simulations; MMPBSA; Podocarflavone A synthesis

SNP discovery and structural insights into OeFAD2 unravelling high oleic/linoleic ratio in olive oil - Ben Ayed, Rayda; Moreau, Fabienne; Ben Hlima, Hajer; Rebai, Ahmed; Ercisli, Sezai; Kadoo, Narendra; Hanana, Mohsen; Assouguem, Amine; Ullah, Riaz; Ali, Essam A. (Computational and Structural Biotechnology Journal, 2022)
Fatty Acid Desaturase 2 (FAD2), a key enzyme in the fatty acid biosynthesis pathway, is involved in the desaturation and conversion of oleic acid to linoleic acid. Therefore, it plays a crucial role in oleic/linoleic acid ratio and the quality of olive oil. DNA sequencing of 19 FAD2 genes from a set of olive oil varieties revealed several single-nucleotide polymorphisms (SNPs) and highlighted associations between some of the SNPs and saturated fatty acids contents. This was further confirmed by SNP-interaction and machine learning approach. Haplotype diversity analysis led to the discovery of three highly polymorphic SNPs and four haplotypes harboring differential oleic/linoleic acid ratios. Moreover, a combination of molecular modeling and docking experiments allowed a deeper and better understanding of the structure-function relationship of the FAD2 enzyme. Sequence patterns and variations involved in the regulation of the FAD2 activity were also identified. Furthermore, S82C and H213N substitutions in OeFAD2 make the Oueslati variety more interesting in terms of fatty acid profile and oleic acid level. (C) 2022 The Authors. Published by Elsevier B.V. on behalf of Research Network of Computational and Structural Biotechnology.
Keywords: docking; Fatty acid desaturase; Haplotype; machine learning; Oleic/linoleic acid ratio; Protein structure

Histidinal-based potent antimalarial agents - Meena, Chhuttan L.; Hingamire, Tejashri; Gupta, Tanya; Deshmukh, Bhagyashree; Karmodiya, Krishanpal; Joshi, Rakesh; Shanmugam, Dhanasekaran; Sanjayan, Gangadhar J. (ChemMedChem, 2023)
Herein we report the synthesis and evaluation of peptide-histidinal conjugated drug scaffolds, which have the potential to target the hemoglobin-degrading proteases falcipain-2/3 from the human malaria parasite. Scaffolds with various substitutions were tested for antimalarial activity, and compounds 8 g, 8 h, and 15 exhibited EC50 values of similar to 0.018 mu M, similar to 0.069 mu M, and similar to 0.02 mu M, respectively. Structure-based docking studies on falcipain-2/3 proteases (PDB:2GHU and PDB:3BWK) revealed that compounds 8 g, 8 h, and 15 interact strongly with binding sites of falcipain-2/3 in a substrate-like manner. In silico ADME studies revealed that the molecules of interest showed no or minimal violations of drug-likeness parameters. Further, phenotypic assays revealed that compound 8 g and its biotinylated version inhibit hemoglobin degradation in the parasite food vacuole. The identification of falcipain-2/3 targeting potent inhibitors of the malaria parasite can serve as a starting point for the development of lead compounds as future antimalarial drug candidates.
Keywords: artemisinin; chloroquine; digestive vacuole; docking; falcipains; falciparum; P

Integrative multi-omics and computer-aided biofungicide design approach to combat fusarium wilt of chickpea - Sahoo, Rosaleen; Kadoo, Narendra Y. (Planta, 2025)
Main conclusionIntegrating multi-omics and computer-aided drug discovery approaches can overcome the limitations of traditional methods and help develop highly effective, specific, and environmentally safe biofungicides to control crop diseases.AbstractChickpea is a valuable legume crop in terms of nutrition, food security, economic sustainability, and environmental benefits. Fusarium wilt caused by the soil-borne fungus Fusarium oxysporum f.sp. ciceri is one of the most important diseases affecting chickpea. Several disease management methods, including crop rotation, soil fumigation with chemical fungicides, soil solarization, etc., are practiced to manage the disease. However, these methods have various limitations and cannot completely control the disease. Moreover, chemical fungicides indiscriminately kill even the beneficial soil microbes, pollute groundwater, and enter the food chain. Hence, modern approaches emphasizing innovative strategies and technologies need to be explored to manage the disease effectively. In this review, we propose integrating multi-omics (genomics, proteomics, metabolomics, etc.) and computer-aided drug discovery (CADD) approaches to develop biofungicides targeting vital pathogen proteins. Multi-omics approaches can delve deeper into the plant-pathogen interaction and reveal essential pathogen genes or proteins. These proteins could be targeted using CADD to identify phytochemical-based potential biofungicides, either using structure- or ligand-based drug design approaches. The potential biofungicides can be subjected to the prediction of carcinogenicity, hepatotoxicity, mutagenicity, etc., to identify biofungicides that are safe to use and are highly specific to the target pathogen. In vivo and in vitro validation studies can be followed to establish the efficacy and safety of the identified biofungicides for their practical application. This integrated approach can reduce the time and cost compared to the traditional methods and accelerate the discovery of highly effective biofungicides to protect crops from various diseases.
Keywords: CADD; docking; Fungal diseases; MD Simulation; Protein structure prediction; Transcriptomics